Islamic Religious Education Model with Environmental Insight at SMA N 2 Demak - Muhammad Aris Faisol; Fatah Syukur; Raharjo Raharjo (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Environmental problems are still the subject of discussion today because the state of the environment over time continues to decline, both in terms of quality and quantity in supporting human life. This research is a type of field research. The approach in this study uses a phenomenological approach. The data sources for this research are person, place, and paper. Data collection techniques using interviews, observation, and documentation. While the data analysis technique used data reduction, data display, and conclusion drawing. The results showed that the Islamic religious education model with an environmental perspective at SMA N 2 Demak uses the 2013 curriculum which is integrated with environmental education. In integrating into Islamic religious education subjects, more emphasis is placed on aspects of the Qur'an, hadith, and fiqh.Â